Preclinical evaluation of avutometinib and defactinib in high‐grade endometrioid endometrial cancer - Tobias Max Philipp Hartwich; Miranda Mansolf; Cem Demirkiran; Michelle Greenman; Stefania Bellone; Blair McNamara; Shuvro P. Nandi; Ludmil B. Alexandrov; Yang Yang‐Hartwich; Silvia Coma; Jonathan Pachter; Alessandro D. Santin (Cancer Medicine)
Abstract Background High‐grade endometrial cancers (EAC) are aggressive tumors with a high risk of progression after treatment. As EAC may harbor mutations in the RAS/MAPK pathways, we evaluated the preclinical in vitro and in vivo efficacy of avutometinib, a RAF/MEK clamp, in combination with the focal adhesion kinase (FAK) inhibitors defactinib or VS‐4718, against multiple primary EAC cell lines and xenografts. Methods Whole‐exome sequencing (WES) was used to evaluate the genetic landscape of five primary EAC cell lines. The in vitro activity of avutometinib and defactinib as single agents and in combination was evaluated using cell viability, cell cycle, and cytotoxicity assays. Mechanistic studies were performed using Western blot assays while in vivo experiments were completed in UTE10 engrafted mice treated with either vehicle, avutometinib, VS‐4718, or their combination through oral gavage. Results WES results demonstrated multiple EAC cell lines to harbor genetic derangements in the RAS/MAPK pathway including KRAS/PTEN/PIK3CA/BRAF/ARID1A, potentially sensitizing to FAK and RAF/MEK inhibition. Five out of five of the EAC cell lines demonstrated in vitro sensitivity to FAK and/or RAF/MEK inhibition. By Western blot assays, exposure of EAC cell lines to defactinib, avutometinib, and their combination demonstrated decreased phosphorylated FAK (p‐FAK) as well as decreased p‐MEK and p‐ERK. In vivo the combination of avutometinib/VS‐4718 demonstrated superior tumor growth inhibition compared to single‐agent treatment and controls starting at Day 9 (p < 0.02 and p < 0.04) in UTE10 xenografts. Conclusions Avutometinib, defactinib, and to a larger extent their combinations, demonstrated promising in vitro and in vivo activity against EAC cell lines and xenografts. These preclinical data support the potential clinical evaluation of this combination in high‐grade EAC patients.